已知xy=2,x-y=3,求(x+y)(x-y)-y^2-(6x^2y-2xy^2)/2y的值.
人气:122 ℃ 时间:2020-03-26 13:51:59
解答
(x+y)(x-y)-y^2-(6x^2y-2xy^2)/2y
=x^2-y^2-y^2-3x^2+xy
=-2(x^2+Y^2)+xy
=-2(x^2+Y^2-2xy)-4xy+xy
=-2(x-y)^2-3xy
=-2*3^2-3*2
=-24
推荐
- 已知x+y=-4,xy=3,求4(xy+2y)+[6x-(2xy-y-3x)]的值
- 已知xy=2,x-y=3,求(x+y)(x-y)-y^2-(6x^2y-2xy^2)/2y的值.
- 已知x+y=4,xy=3,求4{xy+2y}+{6x-[2xy-y-3x}}的值
- 已知xy=2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)/2y的值.
- X+Y=-1,XY=3求5(XY+2Y)+(6X-(2XY+Y-3X))的值
- (2)*-2是多少,
- A s_____ makes shoes.
- 绿叶是生态环境最勇敢的维护者 改成疑问句.
猜你喜欢